PKM Pendampingan Kader Posyandu Dan Ibu Hamil Tentang Sosialisasi dan Pelatihan Senam Hamil Bagi Ibu Hamil Trimester 2 dan 3 Di RW 02 Kelurahan Sambiroto Kecamatan Tembalang Kota Semarang - Fitratun Najizah; Shella Dhika R.; Anisa Mutiara Hanani; Dana Faricha; Lu’luah Feby Purwanti; Ni Kadek Krisna Dwi Patrisia (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Pregnant women really dream of a healthy pregnancy. To be able to have a healthy pregnancy, pregnant women can do pregnancy exercises. An old method that is still used in pregnancy services today is pregnancy exercise, where pregnancy exercise is also a method of relaxation and exercise for pregnant women which is a permanent program in antenatal care, aimed at making pregnant women mentally and physically ready to face the birthing process. In fact, even though there are pregnancy exercises for pregnant women, there are still many who don't know about pregnancy exercises. Based on a preliminary survey of 10 pregnant women with gestational age entering the 2nd and 3rd trimesters who came to the Posyandu regularly in RW 02 Sambiroto Village, there were 4 pregnant women who said that while participating in activities at the Posyandu they only received material regarding pregnancy information. This community service activity is an effort to increase the knowledge, skills and understanding of posyandu cadres and pregnant women about the methods and benefits of pregnancy exercise during the second and third trimesters of pregnancy in RW 02, Sambiroto Village, Tembalang District, Semarang City. The specific target of this PKM is to teach cadres and pregnant women how to do safe pregnancy exercises for the 2nd and 3rd trimester of pregnancy. This PKM program activity is carried out using counseling and training methods at the RW 02 hall, Sambiroto Village with implementation methods a) Pre-field survey, b ) Preparation of training tools and materials, c) Preparation of training methods, d) Training of Posyandu cadres and pregnant women, e) Mentoring, f) Evaluation, g) Making reports and publications. Based on the results of socialization and training, significant results were obtained, namely that posyandu cadres were able to guide pregnancy exercise correctly and pregnant women understood the benefits of pregnancy exercise.